The Mechanism of Oocyte Activation Influences the Cell Cycle-Related Genes Expression During Bovine Preimplantation Development - Milazzotto, Marcella Pecora; Feitosa, Weber Beringui; Paula-Lopes, Fabiola Feitosa; Buratini, Jose [UNESP]; Visintin, Jose Antonio; Assumpcao, Mayra E. O. A. (Mary Ann Liebert, Inc., 2012)
The first cleavage divisions and preimplantation embryonic development are supported by mRNA and proteins synthesized and stored during oogenesis. Thus, mRNA molecules of maternal origin decrease and embryonic development becomes gradually dependent on expression of genetic information derived from the embryonic genome. However, it is still unclear what the role of the sperm cell is during this phase and whether the absence of the sperm cell during the artificial oocyte activation affects subsequent embryonic development. The objective of this study was to determine, in bovine embryos, changes in cell cycle-associated transcript levels (cyclin A, cyclin B, cyclin E, CDC2, CDK2, and CDK4) after oocyte activation in the presence or absence of the sperm cell. To evaluate that, in vitro-produced (IVP) and parthenogenetically activated (PA) embryos (2-4 cells (2-4C), 8-16 cells (8-16C) and blastocysts) were evaluated by real-time PCR. There was no difference in cleavage and blastocyst rates between IVP and PA groups. Transcript level was higher in oocytes than in IVP and PA embryos. Cleaved PA embryos showed higher expression of cyclin A, cyclin B, cyclin E, and CDK2 and lower expression of CDC2 when compared with that from the IVP group. At the time of activation, all transcripts were expressed less in PA than in IVP embryos, whereas at the blastocyst stage, almost all genes were expressed at a higher level in the PA group. These results suggest that in both groups there is an initial consumption of these transcripts in the early stages of embryonic development. Furthermore, 8-16C embryos seem to synthesize more cell cycle-related genes than 2-4C embryos. However, in PA embryos, activation of the cell cycle genes seems to occur after the 8- to 16-cell stage, suggesting a failure in the activation process.